Edukasi Petani tentang Pentingnya Aplikasi Hatch and Carry Elaeidobius kamerunicus untuk Meningkatkan Produksi Kelapa Sawit: Public Education on the Importance of Applying the Hatch and Carry Technique Elaeidobius kamerunicus to Improve Oil Palm Production - Rezki, Dewi; Suhendra, Dede; Heriza, Sri; Sari, Wulan Kumala; Hanum, Alefia Lathifa; Rahman, Muhammad Aulia; Anzalia, Qomara; Hasibuan, Reza Alam Nur; Terence, Tristan; Bifadlika, Faghfirlana; Aditya, Irfan; Ramadhani, Mutiara (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The area of oil palm plantations in Dharmasraya Regency is not in line with the amount of production obtained by farmers. This is due to the large number of parthenocarpic fruits caused by the few pollinators and male flowers, so the pollination process in oil palm plantations is not optimal. This activity aims to train farmers in Koto Beringin Village, Tiumang District. The activity method is carried out through counseling and demonstration plots on applying hatch & carry techniques for Elaeidobius kamerunicus to improve the pollination process so that oil palm production can increase. In this activity, farmers are expected to be able to produce products in the form of oil palm pollen and Elaeidobius kamerunicus breeding cages. From the activities that have been carried out, it is known that farmers' knowledge of hatch & carry techniques for Elaeidobius kamerunicus is still very minimal. Through counseling and demonstration plot activities, farmers have been able to breed Elaeidobius kamerunicus and collect oil palm pollen. From the results of observations in people's oil palm fields, it is known that after the application of the Hatch & Carry technique was carried out, there was an increase in the number of Elaeidobius kamerunicus pollinators from 524 individuals/Ha to 21,137 individuals/Ha and will continue to increase if the application of the Hatch & Carry technique continues to be carried out. If farmers apply the hatch & carry technique of Elaeidobius kamerunicus correctly, it can increase the number of pollinators that play a role in pollination.